The Potential Added Value of Novel Hearing Therapeutics: An Early Health Economic Model for Hearing Loss - Mandavia, Rishi; Horstink, Yvette M; Grutters, Janneke P C; Landry, Evie; May, Carl; Rovers, Maroeska; Schilder, Anne G M; Scholte, Mirre (Otology & neurotology, 2020)
To construct an early health economic model to assess the potential added value of novel hearing therapeutics, compared with the current standard of care. We use idiopathic sudden sensorineural hearing loss (ISSNHL) as a case example, because it is a lead indication for several emerging hearing therapeutics. A decision analytic model was developed to assess the costs and effects of using novel hearing therapeutics for patients with ISSNHL. This was compared to the current standard of care. Input data were derived from literature searches and expert opinion. The study adopted a healthcare perspective of the UK National Health Service. Four analyses were conducted: 1) headroom, 2) scenario, 3) threshold, 4) sensitivity. The decision analytic model showed that novel therapeutics for ISSNHL have potential value both in terms of improved patient outcomes, as well as incremental net monetary benefit (iNMB). The base case analysis revealed an iNMB of £39,032 for novel therapeutics compared with the current standard of care. Results of the threshold and scenario analysis revealed that age of treatment and severity of ISSNHL are major determinants of iNMB for novel therapeutics. This article describes the first health economic model for novel therapeutics for hearing loss; and shows that novel hearing therapeutics can be cost-effective under NICE's cost-effectiveness threshold, with considerable room for improvement in the current standard of care. Our model can be used to inform the development of cost-effective hearing therapeutics; and help decision makers decide which therapeutics represent value for money.